Author Correction: Choosing the future of Antarctica. (11th October 2018) - Rintoul, S.; Chown, S.; DeConto, R.; England, M.; Fricker, H.; Masson-Delmotte, V.; Naish, T.; Siegert, M.; Xavier, J.
On page 234 of this Perspective, '50% decrease' has been corrected online to '50% increase' in the sentence "The pH of surface waters south of 60° S decreased by 0.2 between 2017 and 2070, equivalent to a 50% increase in the concentration of hydrogen ions since the pre-industrial period1 ."